PENGARUH PROFITABILITAS, KEPUTUSAN PENDANAAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Dinda Maulid Rahmawati; LMS Kristiyanti; Sri Laksmi Pardanawati (Jurnal Ilmiah Akuntansi, 2024)
The purpose of this study is to determine the impact of funding, investment, and profitability decisions on the company value of food and beverage companies listed on the IDX between 2019 and 2023. Associative descriptive research using a quantitative approach is used in this sort of study, and secondary data from journals, the corporate website, and yearly financial reports published on the BEI website www.idx.co.id are used as research data sources. Purposive sampling was the method utilized to choose the research sample. Using SPSS 23, multiple linear analysis is the analytical technique employed. The study's findings indicate that: (1) Company value is influenced by funding, investment, and profitability decisions taken collectively. (2) Investment choices and profitability have an impact on a company's worth. (3) The value of the company is unaffected by funding decisions.